Effect of different crop management practices for better economic returns from Kharif onion: Effects of NPKS fertilizer levels and spacing on Kharif onion - Bhardwaj, R L; Parmar, D K; Meena, Jaideep; Vyas, Latika (Journal of Spices and Aromatic Crops, 2022)
The present study was undertaken at the Agricultural Research Substation, Sumerpur-Pali to find out the effect of different fertilizer levels and crop geometry on kharif onion (Allium cepa L.) production. The experiment was laid out in split plot design with NPKS levels as main plot and crop geometry as subplot with three replications. Spacious crop geometry with highest dose of fertilizer (15 cm x 15 cm + 140 N: 80 P: 80 K: 40 S kg ha-1) produced maximum plant height (98.20 cm), leaves plant-1 (20), bulb polar diameter (79.34 mm), equatorial diameter (85.10 mm), bulb weight (137.44 g) and harvest index (51.30) with huge quantity of split/multiplier bulbs (6.54 t ha-1). Marketable yield (43.71 t ha-1), gross return (` 5.25 lakhs), net return (` 4.25 lakhs) and B: C ratio (4.25) were higher in the closer crop geometry (10 cm x 10 cm) with highest dose of fertilizer, whereas maximum biological yield (126.75 t ha-1) and total bulb yield (61.60 t ha-1) were reported in the closest spacing with highest dose of fertilizer (7.5 cm x 7.5 cm + 140 N: 80 P: 80 K: 40 S kg ha-1), which also produced the highest quantity (28.69 t ha-1) of unmarketable bulbs. It is concluded that for maximum production of better quality of kharif onion bulb, the seedlings should be planted at 10 cm x 10 cm spacing with the highest level of fertilizer dose (140 N: 80 P: 80 K: 40 S kg ha-1).